2018
DOI: 10.1111/jam.13902
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electron beam and gamma radiation on drug-susceptible and drug-resistantListeria monocytogenesstrains in salmon under different temperature

Abstract: There are a lot of research on the effect of radiation on the number of bacteria in food products. However, there is almost no information about the effect of strain properties, such as drug susceptibility, virulence, etc., on their resistance to ionizing radiation. An increasing number of drug resistant bacterial strains isolated from food, encourages to take up this research subject.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…For example, Gaougaou et al [ 33 ] observed that in the E. coli O157:H7, γ irradiation at 0.4 kGy dose increased ampC and ampG expression, respectively, by 1.6 and 2-fold in the wild type strain but up to by 2.4 and 3.4-fold when the strain was beforehand adapted to 25 μg/mL of carbenicillin. Likewise, Skowron et al [ 36 ] observed that the antibiotic-resistant L. monocytogenes strains were more resistant to both the β and γ radiations. However, it was observed that the E-beam treatments did not increase or decrease in the expression of virulence genes of L. monocytogenes during the storage time of sliced dry-cured ham [ 37 ].…”
Section: Effects On Microorganisms and Pestsmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, Gaougaou et al [ 33 ] observed that in the E. coli O157:H7, γ irradiation at 0.4 kGy dose increased ampC and ampG expression, respectively, by 1.6 and 2-fold in the wild type strain but up to by 2.4 and 3.4-fold when the strain was beforehand adapted to 25 μg/mL of carbenicillin. Likewise, Skowron et al [ 36 ] observed that the antibiotic-resistant L. monocytogenes strains were more resistant to both the β and γ radiations. However, it was observed that the E-beam treatments did not increase or decrease in the expression of virulence genes of L. monocytogenes during the storage time of sliced dry-cured ham [ 37 ].…”
Section: Effects On Microorganisms and Pestsmentioning
confidence: 99%
“…In general, it is known that microorganisms are more resistant in a frozen medium than in a medium at room temperature, or in a dry medium than in a water-rich medium ( Table 5 ). Skowron et al [ 36 ] reported that for the L. monocytogenes strains the lower the temperature at which the contaminated fillet fragments were exposed to radiation, the higher the theoretical lethal and D 10 doses were, irrespective of the type of radiation.…”
Section: Effects On Microorganisms and Pestsmentioning
confidence: 99%
See 2 more Smart Citations
“…The resistance to irradiation of microorganisms may increase as a result of their adaptation to the stress conditions. Certain resistance genes to specific antibiotics may help some of the pathogenic bacteria to tolerate higher doses of irradiation (Gaougaou et al, 2018;Skowron et al, 2018). Also, sensitivity of bacteria to irradiation, depends upon the growth phase.…”
Section: Effects Of Irradiation On Microbiological Contaminants Of Foodsmentioning
confidence: 99%